HUBUNGAN NYERI KEPALA PRIMER DENGAN PENINGKATAN TEKANAN DARAH DALAM KEHAMILAN - Raden Ajeng Dwi Pujiastuti, Khairul Surbakti, Hasan Sjahrir (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION MIGRENE AND OTHER PRIMARY HEADACHES ARE CONSIDERED TO BE VASCULAR INVOLVING HEADACHES SOME STUDIES SUGGESTED THAT MIGRENE AND OTHER HEADACHES IS RELATED TO ELEVATED BLOOD PRESSURE DURING PREGNANCY AND CONSIDERED TO BE A RISK FACTOR TO PREECLAMPSIA